Sonophore labeled RGD: a targeted contrast agent for optoacoustic imaging - Katja Haedicke; Christian Brand; Murad Omar; Vasilis Ntziachristos; Thomas Reiner; Jan Grimm (Photoacoustics, 2017)
Optoacoustic imaging is a rapidly expanding field for the diagnosis, characterization, and treatment evaluation of cancer. However, the availability of tumor specific exogenous contrast agents is still limited. Here, we report on a small targeted contrast agent for optoacoustic imaging using a black hole quencher® (BHQ) dye. The sonophore BHQ-1 exhibited strong, concentration-dependent, optoacoustic signals in phantoms, demonstrating its ideal suitability for optoacoustic imaging. After labeling BHQ-1 with cyclic RGD-peptide, BHQ-1-cRGD specifically bound to αvβ3-integrin expressing glioblastoma cell spheroids in vitro. The excellent optoacoustic properties of BHQ-1-cRGD could furthermore be proven in vivo. Together with this emerging imaging modality, our sonophore labeled small peptide probe offers new possibilities for non-invasive detection of molecular structures with high resolution in vivo and furthers the specificity of optoacoustic imaging. Ultimately, the discovery of tailor-made sonophores might offer new avenues for various molecular optoacoustic imaging applications, similar to what we see with fluorescence imaging.